Characteristics of Breast Cancer in Men: A Single Case Analysis and Literature Review: Breast Cancer in Men: A Single Case - Andrianarison, Lofo Heriniaina; O. R., Randriarimanana; V. F. , Ranaivomanana; N. S. , Randrianjafisamindrakotroka (International Journal For Research In Biology & Pharmacy, 2022)
Breast cancer in men is a rare condition. It accounts for 1% of all diagnosed breast cancers worldwide and 1.5% of cancers affecting the male gender. Its clinical and morphological features as well as management are more or less similar to those found in women.We report the case of a 55-year-old man who presented with a nodule in the UIQ of the right breast following a chest trauma a few months earlier. Histological examination revealed invasive ductal carcinoma, Grade II (2 + 2 + 2) as per Elston and Ellis, Stage II (pT2Nx) on excisional biopsy. A mastectomy with lymph node excision was carried out. There was no residual tumor and all the lymph nodes were non-metastatic. Male breast cancer is also often associated with a mutation in the BRCA2 gene. Mammography and histology are the key diagnostic examinations. Recurrence and risk of developing other cancers are increased, especially in cases of genetic mutation. Monitoring of patients with such condition is therefore necessary.